2011
DOI: 10.1111/j.1537-2995.2011.03289.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative distribution of West Nile virus RNA in blood compartments: implications for blood donor nucleic acid amplification technology screening

Abstract: The improved sensitivity of WNV NAT using whole blood instead of plasma was confirmed, but appears to be limited to better detection in seropositive stages. However, the implication of these findings for blood screening requires further study to establish the infectivity of persistent whole blood viremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Another possible explanation for antibody persistence is persistent viral infection. This has been suggested by viral RNA detection in human whole blood out to 90 days postinfection, nucleic acids in tissues in a mouse model out to 6 months, and RNA detection in urine from previously infected humans out to 6 years (16)(17)(18). However, others have not been able to verify the latter finding (19).…”
Section: Discussionmentioning
confidence: 79%
“…Another possible explanation for antibody persistence is persistent viral infection. This has been suggested by viral RNA detection in human whole blood out to 90 days postinfection, nucleic acids in tissues in a mouse model out to 6 months, and RNA detection in urine from previously infected humans out to 6 years (16)(17)(18). However, others have not been able to verify the latter finding (19).…”
Section: Discussionmentioning
confidence: 79%
“…17 Briefly, RNA was extracted from undiluted thawed plasma and whole blood samples, and washed PBMCs (to remove any trace of DMSO) using the Qiagen Viral RNA kit (Qiagen) with procedures slightly modified from the package insert. Viral RNA was extracted from 100 μl of plasma or whole blood samples and from 10 × 10 6 PBMCs (thawed, washed with 500 μL of Phosphate-buffered saline (PBS) and resuspended in 100 μL of PBS).…”
Section: Methodsmentioning
confidence: 99%
“…16 and was recently further characterized by Lai et al 17 in a longitudinal cohort of 10 WNV-infected blood donors from Blood Systems. Notably, WNV RNA concentrations were consistently greater in whole blood than in plasma after seroconversion, and viral RNA was detected in whole blood up to 200 days after initial detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, have demonstrated that a large proportion of West Nile virus (WNV) is bound to red blood cells (RBCs) and have shown that WNV RNA concentrations in seropositive donations are 10-fold higher in WB than in plasma and persist for a much longer period of time [11][12][13]. For diagnostic purposes, we demonstrated very recently that WNV RNA can be identified by qRT-PCR in 86.8% of WB samples but only in 26% of serum samples during acute infection [14].…”
Section: Discussionmentioning
confidence: 99%